2020
DOI: 10.3748/wjg.v26.i32.4833
|View full text |Cite
|
Sign up to set email alerts
|

Features of extrahepatic metastasis after radiofrequency ablation for hepatocellular carcinoma

Abstract: BACKGROUND Extrahepatic metastasis (EHM) of hepatocellular carcinoma (HCC) is associated with poor outcomes. However, the clinical features and risk factors of EHM of HCC after radiofrequency ablation (RFA) remain unclear. AIM To elucidate the characteristics and risk factors of EHM after RFA for HCC. METHODS From January 2008 to December 2017, we retrospectively enrolled 661 patients who underwent RFA as first-line treatment for HCC at 2 ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
4
12
2
Order By: Relevance
“…Recent studies have shown that high AFP levels were independent risk factors of HCC invasiveness 27 30 . Similarly, our previous study on EHR in RFA for HCC also demonstrated an association between the AFP level and HCC recurrence when the AFP level was > 400 IU/mL, in line with our findings 17 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Recent studies have shown that high AFP levels were independent risk factors of HCC invasiveness 27 30 . Similarly, our previous study on EHR in RFA for HCC also demonstrated an association between the AFP level and HCC recurrence when the AFP level was > 400 IU/mL, in line with our findings 17 .…”
Section: Discussionsupporting
confidence: 93%
“…Another study identified IHR as the most common initial site of recurrence, with EHR developing after several treatments for IHR 19 . Uchino et al reported that 82.2% of patients with HCC with EHR presented with IHR, a finding comparable to those of our previous study 17 . Therefore, multiple IHRs may indicate EHR risk in patients with HCC 20 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another study identi ed IHR as being the most common initial site of recurrence, with EHR developing after several treatments for IHR [21]. Uchino et al reported that 82.2% of HCC patients with EHR presented with IHR, a nding comparable to those of our previous study [19]. Therefore, multiple IHRs can be an indication of EHR risk in patients with HCC [22].…”
Section: Analysis Of Factors Associated With Ehrsupporting
confidence: 79%
“…Current results of HCC recurrence and EHR development rates suggest some distinction from our previous study of HCC patients who underwent RFA [19]. In that study, the median time to rst HCC recurrence and EHR after RFA was 1.75 years and 2.68 years, respectively, with 1-, 3-, 5-, 8-, and 10-year rates of EHR development of 1.0%, 2.9%, 8.1%, 15.7%, and 33.7%, respectively.…”
Section: Discussioncontrasting
confidence: 57%